PANDANGAN AT-TUFI DAN ASY-SYATIBI TENTANG MASLAHAT (Studi Analisis Perbandingan) - Basri, Rusdaya (DIKTUM: Jurnal Syariah dan Hukum, 2011)
This article discusses the problem of view at-Tufi and ash-Syatibi of beneficiaries: Comparative Study. Well-being of slaves, is a determinant factor of the study of the theory of benefit to at-Tufi and as-Syatibi. The main focus of this discussion with literature approach. The results of a literature review indicates that the concept of beneficiaries in view of at-Tufi and ash-Syatibi arguments are based on passages that Shari'a goal is to realize the benefit of both in this world and hereafter. The scope of beneficiaries are at-Tufi and as-Syatibi on issues soaial life and customs, does not apply to matters of worship and the measures that have been established Personality '. For at-Tufi, beneficiaries is a separate argument beyond the sacred text, it means masalahat not have supported the text. Because is independent, if contrary to nat / text then prioritized beneficiaries through takhsis, while the ash-Syatibi beneficiaries understand the universal nature which is the result of induction of the arguments of Personality 'so that if the beneficiaries are partial/juz' i conflict with the universal beneficiaries who precedence is the beneficiaries who are universal because of its qat'i. This difference has implications for the epistemological differences. Epistemologically, at-Tufi quite liberal in understanding the theory of beneficiaries because it puts the reasonable opinion higher than revelation or tradition. For at-Tufi, because the basis of Islamic Shari'a is the benefit, and the beneficiaries themselves can be achieved in determining the sense that something is not necessary mafsadat beneficiaries or revelation or tradition, but the reasoning is quite reasonable. While trying to integrate Syatibi ash-revelation and reason through the application of inductive logic of Islamic texts in understanding the theory of benefit.